Low to High Intensity Exercise dalam Menurunkan Kadar Gula Darah pada Pasien DM Tipe 2 - Muhammad Alghifari Budiman; Iqbal Pramukti; Nursiswati Nursiswati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to map and synthesize evidence regarding the effectiveness of low to high-intensity exercise in reducing blood sugar levels in type 2 DM patients according to patient characteristics. The method used is a scoping review with a search strategy using the PICO(s) format. Pubmed, Science Direct, CINAHL, and the Google Scholar search engine are the databases used. The research results showed that eight articles were in English, five studies showed a significant reduction in blood sugar, and three others showed no significant decrease. Apart from that, it was also found that there was an increase in insulin, which showed a significant increase in HbA1c, and there was no increase in the dose of anti-diabetic therapy. Several types of exercise are used at all intensities depending on the patient's ability, including walking, jogging, power cycling, and walking on a treadmill. In conclusion, exercise can reduce weight for obese patients and increase muscle strength, followed by improved physical function for patients with weight loss. Keywords: Diabetes Mellitus Type 2, Exercise Therapy, Blood Glucose